Pendidikan Islam Pada Masa Dinasti Saljuk: Madrasah Nizamiyah - Azan Rizkian Jaya; M. Nurul Humaidi (IAIN Bengkulu, 2023)
The birth of madrasah as an educational institution in this era can not be separated from the history of the development of madrasah in the past. Before Muslims knew madrasah educational institutions, Muslim educational institutions were still known by the terms suffah, kuttab or maktab and mosque. So that from these educational institutions were born various expert scholars from various fields both in the field of religion and other fields of science. Around the end of the 4th century AH the Saljuk Dynasty was led by Sultan Alp and Malik Syah who had a very famous vizier named Nizam al-Mulk succeeded in establishing the first madrasah educational institution called Madrasah Nizamiyah. Madrasah Nizamiyah is the first Islamic educational institution in the form of a school under the auspices of the government, so that the government has a major stake in its development process. In this discussion, the author focuses on deepening the concept of Madrasah Nizamiyah education under the auspices of the Saljuk Dynasty, as well as the concept of education which is widely referred to in the development of Islamic education in the future. Lahirnya madrasah sebagai lembaga pendidikan pada era ini tidak bisa lepas dari sejarah berkembangnya madrasah pada masa lampau. Sebelum umat Islam mengenal lembaga pendidikan madrasah, lembaga pendidikan umat Islam masih dikenal dengan istilah suffah, kuttab atau maktab serta masjid. Sehingga dari lembaga pendidikan tersebut lahirlah berbagai ulama-ulama ahli dari berbagai macam bidang baik dalam bidang keagamaan maupun bidang ilmu lainnya. Pada sekitar akhir abad ke-4 hijriah Dinasti Saljuk dipimpin oleh Sultan Alp dan Malik Syah yang memiliki wazir yang sangat masyhur yang bernama Nizam al-Mulk berhasil mendirikan institusi pendidikan madrasah pertama yang bernama Madrasah Nizamiyah. Madrasah Nizamiyah meruakan institusi pendidikan Islam pertama yang berbentuk sekolah dibawah naungan pemerintahan, sehingga pemerintah memiliki andil besar dalam proses perkembangannya. Dalam pembahasan ini penulis fokus mendalami konsep pendidikan Madrasah Nizamiyah dibawah naungan pemerintahan Dinasti Saljuk, serta konsep pendidikannya yang banyak dirujuk dalam perkembangan pendidikan Islam pada masa berikutnya.